Effects of Additives on the Performance of Drag Reduction Agents - Chen Ming Hui, Chen (Universiti Teknologi Petronas, 2012)
Friction that occurs in the pipeline causes pressure drop and the decrease in flow rate of the fluid. This happens when a moving fluid completely stops at the pipe surface and assumed to experience zero velocity in relative to the pipe surface in a stationary pipeline. Fluid which contacts directly with the pipe “sticks” to the pipe surface because of the viscous effects. The adjacent fluid layer is being slowed down by the layer that sticks to the surface due to the viscous forces between the fluid layers. The additions of Drag Reduction Agents (DRA) are being used worldwide to overcome this problem. This study is intended to explore and compare the compatibility of additives which were added into the commercial DRA in different concentrations using the AR-G2 Double Concentric Cylinder (DCC) rheometer from TA Instruments. This study is important as power resources is one of the major concerns in the modern industrial development. Turbulent mode of liquid transported through pipelines often caused pumping power losses which is not economical. The flow rate of the liquid in the pipeline can be increased with the use of DRA without changing the mechanical parts of the process such as the size of the pipeline, the speed of the pump etc. Torque, which is one of the rheometer operating variables, has been measured experimentally on working fluids with the increase of angular velocity. The performance of DRA is directly linked to the magnitude of the drag reduction percentage (%DR) by utilizing the torque measured from the rheometer. This new method of evaluating the performance of DRA showed great potential in replacing the current flow loop study method with the small amount of sample required (~10 ml), large testing temperature range up to 200°C and pressure cell testing facility up to 2000 psi besides its rapidity. Experimental results showed that the presence of additives such as Xanthan gum and filtration control agent in water soluble DRA does not help in the performance of DRA. However, Pour Point Depressants (PPD) showed great compatibility with the oil soluble DRA where great effects of drag reduction was observed compared to the DRA alone.